Group Consumption with Caring Individuals. Issue 627 (10th September 2019) - Cherchye, Laurens; Cosaert, Sam; Demuynck, Thomas; De Rock, Bram
Abstract: We propose a novel approach to model joint consumption decisions of individuals who care for each other. The model encompasses a continuum of group consumption models situated between the fully co-operative model and the non-cooperative model without caring. We also define a measure for the degree of intragroup cooperation that quantifies how close the observed group behaviour is to fully co-operative behaviour. Following a revealed preference approach, we derive testable implications of the model for empirical data. We use our model to analyse decisions made by children in an experimental setting.